Molecular characterisation of Hepatozoon aegypti Bashtar, Boulos & Mehlhorn, 1984 parasitising the blood of Spalerosophis diadema (Serpentes: Colubridae) - Abdel-Haleem, Heba M.; Mansour, Lamjed; Holal, Mohamed; Qasem, Mahmood A. A.; Al-Quraishy, Saleh; Abdel-Baki, Abdel-Azeem S. (Parasitology research (1987), 2018)
Hepatozoon aegypti Bashtar, Boulos & Mehlhorn, 1984 was first described from the blood of the diadem snake ( Spalerosophis diadema ) in Egypt. During an investigation of the diversity of reptilian haemogregarines in Saudi Arabia, seven diadem snakes (100% of the sample) were found to be highly parasitised by H. aegypti , with an average parasitaemia of 37% per 500 counted erythrocytes. A complete characterisation of this species with morphometrics and 18S rDNA sequence data is therefore presented here. The infection was found to be restricted to the erythrocytes with, frequently, single and, sometimes, double infections. Mature gamonts were sausage-shaped with round posterior and anterior extremities and measured 14 (13–17) × 3.5 (3–5) μm. The infected erythrocytes were hypertrophied with a faintly stained cytoplasm and longitudinally stretched nuclei. The merogonic stages occurred only in the endothelial cells of the snakes’ lungs, and no stages were found in other organs. Mature meronts were round in shape, measured 18 (17–21) μm in diameter and were estimated to produce between 9 and 15 merozoites. Phylogenetic analysis based on the partial 18S small subunit ribosomal DNA sequences indicates that Hepatozoon aegypti cluster within a mixed clade of Hepatozoon species parasitising snakes, geckos and rodents from various geographic areas. Our results might reinforce the theory of prey-predator transmission in respect to the relationships of snake-host Hepatozoon species.